Concept of the study of art by R.J. Collingwood as an object of theoretical analysis - M. V. Ternova (Ukrainian Cultural Studies, 2020)
The article analyzed concept of the study of art by Robin George Collingwood (1889-1943), a well-known English neo-hegelian philosopher. His significant part of the theoretical heritage is connected with the explanation of the nature of art and with the consideration of its condition during the period of the changing Oscar Wilde era to the era of Rudyard Kipling. The circle of problem such as content and form, character, image, mimesis, reflection, emotion, art and "street man" identified. All of them in Collingwood’s presentation and interpretation significantly expanded the space of research not only English, but also European art criticism. The concept of study of art is "built" on the basis of an active understanding of historical and cultural traditions accented. The concept of art criticism of R.G. Collingwood – a famous English philosopher of the XIX-XX centuries, on the one hand, has self-importance, and on the other, although based on the traditions of contemporary humanities, still expands art history analysis of aesthetics through aesthetics and psychology. Recognizing the exhaustion of the English model of romanticism, R.G. Collingwood tries to outline the prospects for the development of art in the logic of the movement "romanticism – realism – avant-garde", which leads to the actualization of the problem of "mimesis – reflection". At the same time, the theorist’s attention is consciously concentrated around the concept of "subject", the understanding of which is radically changing at the turn of the XIX-XX centuries. Theoretical material in the presentation of R.G. Collingwood is based on the work of Shakespeare, Reynolds, Turner, Cezanne, whose experience allows us to focus on the problem of "artist and audience". It is emphasized that Collingwood’s position is ahead of its time, stimulating scientific research in the European humanities. The existence of indicative tendencies, which are distinguished in the logic of European cultural creation of the historical period, is emphasized.